Prison ship records from the War of 1812. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2014)
This collection contains prison ship records drawn from the War of 1812, an inconclusive military conflict between the United States and Great Britain. The War of 1812 was incited by British attempts to restrict U.S. trade, the Royal Navy's impressment of American seamen, and the American desire to expand its territory. Although war changed little between the two Great Powers, it did lead to significant symbolic events like the burning of Washington and inspired the poem that led to the United States' national anthem, "The Star Spangled Banner". The records are drawn from British administered prisoner of war ships and their corresponding ports, which ranges from English towns like Plymouth, to colonial ports like Barbados in the West Indies. Information provided by the shipping records includes the place of birth of prisoners, the health of the prisoners, and the port that their respective prison ships docked at. Overall, this collection offers a window into how prison populations were managed by their captors in wartime.
Date range: 1812-1815.
Keywords: Prisoners of war -- Massachusetts -- Plymouth -- History -- 19th century; Prisoners of war -- United States -- History -- 19th century